Maternal cardiac disease-peripartum management. (16th November 2010) - Parasuraman, R; Kerr, J; Veldtman, GR; Howe, DT
Abstract : Objectives: Maternal cardiac disease is now the single commonest cause of death in pregnancy accounting for 48 maternal deaths in the last triennium. Our aim was to audit the documentation of peripartum management plan in women with cardiac disease. Standards: (1) 100% documentation of a clear plan of care for delivery and immediate postpartum period. (2) The plan must be easily accessible in the obstetric notes on the delivery plan sheet. Methods: The authors performed a retrospective review of 15 patient records. All of them had congenital heart disease and have been seen in our joint cardiac-obstetric clinic at the Princess Anne Hospital. Results: Clear diagnosis of the cardiac condition was documented in 93%. Planned mode of delivery was documented in 93% with second stage management specified in 87%. Recommendations for the third stage were mentioned in 20%. Need for antibiotic prophylaxis was noted in 73%. An anaesthetic plan was described in 93% but requirement for maternal invasive monitoring noted only in 60%. Thromboprophylaxis was documented only in 13% and none had a plan for postnatal management. These specific details were contained in various letters and the information was not summarised on the current cardiac delivery proforma. Actions: Following on from our recommendations, the authors have also implemented a guideline 'Cardiac disease in pregnancy' which incorporates a revised delivery plan sheet that included obstetric, cardiac and anaesthetic issues with a clear section for intrapartum and postpartum management. The authors plan to reaudit six months after implementation of the guideline.